2023
DOI: 10.14744/tjtes.2023.84308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amifostine against Blunt Chest Trauma-Induced Cardiac Injury in Rats

Abstract: BACKGROUND:This study aimed to examine whether two different doses of dexamethasone (DXM), which is a corticosteroid, and amifostine (AMI), which reduces cumulative tissue toxicity induced by cisplatin in advanced-stage cancer patients, have ameliorative effects on pathologic changes associated with cardiac contusion (CC) induced in rats. METHODS:Forty-two Wistar albino rats were equally divided into six groups (n=7): C, CC, CC+AMI 400, CC+AMI 200, CC+AMI+DXM, and CC+DXM. Tomography images and electrocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…5,6 Experimental studies have shown that there are numerous ECG changes following decompression that are due to both the direct effect of the trauma on the myocardium and the prolonged muscle injury. [7][8][9] These changes include increased heart rate, ST segment elevation, ST segment depression, prolonged PR interval, T wave changes, arrhythmias, abnormal Q wave, QT prolongation, wide QRS wave. [7][8][9] In people trapped under rubble in earthquakes, adverse effects on the heart may occur as a result of hypovolemia, increased sympathetic activity, many electrolytes released into the blood after muscle injury, free radicals, and triggering of cytokines and various hormonal pathways as a result of immune system activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Experimental studies have shown that there are numerous ECG changes following decompression that are due to both the direct effect of the trauma on the myocardium and the prolonged muscle injury. [7][8][9] These changes include increased heart rate, ST segment elevation, ST segment depression, prolonged PR interval, T wave changes, arrhythmias, abnormal Q wave, QT prolongation, wide QRS wave. [7][8][9] In people trapped under rubble in earthquakes, adverse effects on the heart may occur as a result of hypovolemia, increased sympathetic activity, many electrolytes released into the blood after muscle injury, free radicals, and triggering of cytokines and various hormonal pathways as a result of immune system activation.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] These changes include increased heart rate, ST segment elevation, ST segment depression, prolonged PR interval, T wave changes, arrhythmias, abnormal Q wave, QT prolongation, wide QRS wave. [7][8][9] In people trapped under rubble in earthquakes, adverse effects on the heart may occur as a result of hypovolemia, increased sympathetic activity, many electrolytes released into the blood after muscle injury, free radicals, and triggering of cytokines and various hormonal pathways as a result of immune system activation. The negative effects of the earthquake on the heart and the increase in cardiovascular events persist not only at the time of the earthquake, but also in the months that follow.…”
Section: Discussionmentioning
confidence: 99%
“…Основными патогенетическими факторами посттравматического периода ушиба сердца являются циркуляторная гипоксия и нарушение течения энергозависимых процессов [1,2] в совокупности с механическим повреждением, приводящие к накоплению в кардиомиоцитах поврежденных органелл, несвернутых белков, лактата, ионов Ca 2+ , а также к нехватке субстрата для поддержания необходимого уровня гомеостаза и запуска репаративных процессов [3][4][5]. На моделях ишемического повреждения миокарда эти факторы описаны как триггеры, способные привести к увеличению активности феномена аутофагии -одного из вариантов запрограммированной клеточной гибели, суть которого заключается в деградации поврежденных органелл с целью дальнейшего использования их клеткой для восстановления метаболизма и формирования новых функционально полноценных структур [6].…”
Section: Introductionunclassified